Effectiveness of simulation-based learning using “e-archive” technology in the archiving subject vocational school - Sigit Permansah; Cicilia Dyah Sulistyaningrum Indrawati; Muhtar Muhtar; Dede Rusmana (Institute of Advanced Engineering and Science, 2023)
This study aimed to assess the effectiveness of the simulation-based learning model using “e-archive” technology in the archiving subject in the vocational school of management program. A randomized pretest-posttest control group design and 144 students from Central Java, Indonesia were employed in this quasi-experimental study. The data were analyzed by using the independent sample t-test to determine whether there was a significant mean difference between the experimental class and the control class. The results of this study indicated that the experimental class with the simulation-based learning model using e-archive technology gets better scores than the control class using the conventional learning model. The pretest t-test results in a score of 0.139, while the posttest results in a score of 0.000. We concluded that the simulation-based learning model using e-archive technology is effective and suitable for use in vocational schools, with implications for enhancing student learning results.